Graphene reinforced ultra high molecular weight polyethylene with improved tensile strength and creep resistance properties - A. Bhattacharyya; S. Chen; M. Zhu (eXPRESS Polymer Letters)
Reduced graphene oxide or graphene was dispersed in ultra high molecular weight polyethylene (UHMWPE) using two methods to prepare nanocomposite films. In pre-reduction method, graphite oxide (GO) was exfoliated and dispersed in organic solvents and reduced to graphene before polymer was added, while reduction of graphene oxide was carried out after polymer addition for in situ reduction method. Raman spectroscopic study reveals that the second method results in better exfoliation of graphene but it has more amorphous content as evident from selected area electron diffraction (SAED) pattern, wide angle X-ray and differential scanning calorimetry (DSC). The nanocomposite film produced by prereduction method possesses higher crystallinity (almost the same as that of the pure film) as compared to the in situ method. It shows better modulus (increased from 864 to 1236 MPa), better strength (increased from 12.6 to 22.2 MPa), network hardening and creep resistance (creep strain reduced to 9% from 50% when 40% of maximum load was applied for 72 h) than the pure film. These findings show that graphene can be used for reinforcement of UHMWPE to improve its tensile and creep resistance properties.